Acute and cumulative increases in rotator cuff tendon thickness` in elite swimmers - McKenzie, A.; Hams, A.; Horan, S.; Porter, K.; Duhig, S. (Journal of Science and Medicine in Sport, 2024)
Introduction: Shoulder pain is the most prevalent musculoskeletal complaint of swimmers, with supraspinatus and subscapularis tendon abnormalities being the most implicated structures. Previous research has demonstrated increases in supraspinatus tendon thickness following a single swimming training session. However, it is not known if this acute response to loading is an adaptive or maladaptive phenomenon. Additionally, it is not known if the training response accumulates across the training week. Poolside ultrasonography is a fast and reliable measure of tendon thickness, however challenging in practice. Therefore, we also investigated if poolside strength measures are a reliable proxy for acute tendon morphology changes. Methods: Sixteen elite swimmers, engaged in full-unmodified training and reporting <4/10 pain during strenuous exercise were recruited. Researchers attended two training sessions (early and late in the training week) to collect tendon thickness and strength data immediately before and after each swim. Supraspinatus and subscapularis tendon images were captured poolside using B-mode ultrasound, and peak isometric internal and external shoulder rotation strength were measured using a ForceFrame. A linear mixed model was used to determine the effect of swimming training on tendon thickness and isometric strength. Partial eta squared (?p2) was calculated to determine effects sizes. Post-hoc pairwise comparisons, with Bonferroni corrections, were conducted to determine the effect of a single session (baseline to post-session 1) and the cumulative effect throughout the training week (baseline to post-session 2). Results: Swimming training significantly increased supraspinatus (F(3, 98) = 27.358, p < .001, ?p2 = 0.46) and subscapularis tendon thickness (F (3, 98) = 17.207, p < .001, ?p2 = 0.35). Conversely, swim training had no significant effect on internal (F(3, 98) = 0.980, p = .405, ?p2 = 0.03) or external rotation strength (F(3, 98) = 0.620, p = .604, ?p2 = 0.02). Post-hoc analyses revealed significant increases in tendon thickness following session 1: supraspinatus = +0.35mm (4.64%), SE = 0.09mm, p = .003; subscapularis = +0.32mm (4.98%), SE = 0.09mm, p = .003. Cumulative increases in tendon thickness were seen throughout the training week: supraspinatus = +0.78mm (10.2%), SE = 0.09mm, p <.001; subscapularis = +0.64mm (10.2%), SE = 0.09mm, p < .001. Discussion: Supraspinatus and subscapularis tendon thicknesses increased approximately 5% in a single session, and 10% throughout the elite swimmer`s training week. The observed cumulative increase in tendon thickness may indicate inadequate recovery between sessions. Due to the exclusion of injured swimmers, the impact of the volumetric changes on tendon health are beyond the scope of the current study. However, findings may have implications for training timing, recovery and the high prevalence of tendinopathy observed. Conversely, isometric shoulder strength did not change throughout the training week suggesting the weekly strength monitoring may have little clinical utility in monitoring tendon changes. Impact/Application to the field: The rotator cuff tendons of elite swimmers display acute and cumulative changes in morphology, potentially indicating under-recovery. Peak isometric shoulder rotation strength does not appear to be an accurate proxy to assess acute (daily-to-weekly) morphological changes in rotator cuff tendon. Declaration: My co-authors and I acknowledge that we have no conflict of interest of relevance to the submission of this abstract.